2018
DOI: 10.1002/lary.27630
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life after extended versus transsellar endoscopic skull base surgery from 767 patients

Abstract: Objectives/Hypothesis The aim of this study was to compare sinonasal‐related quality of life (QOL) in patients treated by extended or transsellar endoscopic skull base surgery. Study Design Prospective data analysis. Methods Prospectively collected data from patients who underwent endoscopic skull base surgery between 2012 and 2017 were analyzed. Primary outcomes were preoperative Sino‐Nasal Outcome Test‐20 (SNOT‐20) scores and then 1‐month, 3‐month, and 6‐month follow‐up. Comparative analysis was performed be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 18 publications
0
21
0
Order By: Relevance
“…Overall, the use of a NSF for skull base reconstruction can lead to additional morbidity due to the sinonasal complications associated with this technique. A recent review of over 700 patients who underwent endoscopic skull base surgery found that the use of a NSF conferred additional sino-nasal morbidity post-operatively, and had a negative impact on the sino-nasal quality of life outcomes of patients ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, the use of a NSF for skull base reconstruction can lead to additional morbidity due to the sinonasal complications associated with this technique. A recent review of over 700 patients who underwent endoscopic skull base surgery found that the use of a NSF conferred additional sino-nasal morbidity post-operatively, and had a negative impact on the sino-nasal quality of life outcomes of patients ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the use of a NSF for skull base reconstruction can lead to additional morbidity due to the sinonasal complications associated with this technique. A recent review of over 700 patients who underwent endoscopic skull base surgery found that the use of a NSF conferred additional sinonasal morbidity post-operatively, and had a negative impact on the sino-nasal quality of life outcomes of patients (41). The NSF is an effective, versatile technique that has gone on to form the basis of skull base reconstruction protocols in a number of high-volume skull base centers the world over, with some modifications which will be explored in the sections that follow.…”
Section: Pedicled Nasoseptal Flapmentioning
confidence: 99%
“…Regarding the last point, [2] compared the impact of nasal symptoms and QOL using the sinonasal symptoms test RSOM-31 and QOL test SF-36. They found that patients undergoing extended endoscopic skull base surgery showed higher sinonasal symptoms that patients undergoing pituitary surgery, and both had mild impairment QOL assessed by the SF-36 questionnaire [52] showed a temporary worsening during the first year of postoperative ESBS, after which QOL recovers and returns almost to normal [53] in a single-center prospective cohort study of patients with endoscopic transsphenoidal skull base surgery conclude that sinonasal quality of life worsened after 1 month postoperatively but returned to preoperative levels after the second month and remained stable after 5 months of follow up [54] also reported a recovery of QOL after 6 months of ESBS [55] in a prospective cohort study with 145 patients with both malignant and benign sinonasal tumors, found a statistically significant improvement in SNOT-22 score from baseline to 2 years [56] observed that extended procedures and NSF usage was significantly associated with poor outcomes.…”
Section: Quality Of Lifementioning
confidence: 96%
“…Although the NSF is the most effective method for grade I to III leaks, a NSF can negatively impact the patient' s sinonasal quality of life and olfactory function [6,7]. Therefore, NSF should only be used when absolutely necessary, such as in grade II or grade III leaks in patients with other risk factors.…”
Section: General Principles Of Endoscopic Skull-base Reconstructionmentioning
confidence: 99%